2017
DOI: 10.1103/physrevb.95.085425
|View full text |Cite
|
Sign up to set email alerts
|

Control of the dipole layer of polar organic molecules adsorbed on metal surfaces via different charge-transfer channels

Abstract: Abstract:Organic molecules with a permanent electric dipole moment have been widely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 53 publications
4
38
0
Order By: Relevance
“…Chloroaluminium Phthalocyanine (ClAlPc), have received much attention due to its applications in electronic devices [8,9], especially as its two different adsorption configurations, Cl-up and Cl-down (see Figure 1), allow the tuning of the energy level alignment (ELA) that is crucial for charge-transport performance [10]. Manipulation of the dipole-up and dipole-down configurations of polar MPcs has shown to be possible by choosing different growing conditions or experimental techniques [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chloroaluminium Phthalocyanine (ClAlPc), have received much attention due to its applications in electronic devices [8,9], especially as its two different adsorption configurations, Cl-up and Cl-down (see Figure 1), allow the tuning of the energy level alignment (ELA) that is crucial for charge-transport performance [10]. Manipulation of the dipole-up and dipole-down configurations of polar MPcs has shown to be possible by choosing different growing conditions or experimental techniques [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [13] successfully correlated the MES obtained by photoemission spectroscopy to the density of states (DOS) for the Cl-up and Cl-down configurations of ClAlPc. It was also demonstrated that the dipole orientation of the first ClAlPc layer can be controlled by adjusting the deposition rate and post annealing conditions with the ELA of the two adsorption modes of ClAlPc differing by ∼0.4 eV.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations